A Large Subgroup of Mild-to-Moderate Asthma Is Persistently Noneosinophilic - McGrath, Kelly Wong (American Thoracic Society, 2012)
Rationale: Airway eosinophilia is typical of asthma, and many controller treatments target eosinophilic disease. Asthma is clinically heterogeneous, however, and a subgroup of people with asthma do not have airway eosinophilia. The size of this subgroup is uncertain because prior studies have not examined repeated measures of sputum cytology to determine when people with asthma have intermittent versus persistent sputum eosinophila and when they are persistently noneosinophilic. Objectives: To determine the prevalence and clinical characteristics of the noneosinophilic asthma phenotype. Methods: We analyzed sputum cytology data from 995 subjects with asthma enrolled in clinical trials in the Asthma Clinical Research Network where they had undergone sputum induction and measures of sputum cytology, often repeatedly, and assessment of responses to standardized asthma treatments. Measurements and Main Results: In cross-sectional analyses, sputum eosinophilia (≥2% eosinophils) was found in only 36% of subjects with asthma not taking an inhaled corticosteroid (ICS) and 17% of ICS-treated subjects with asthma; an absence of eosinophilia was noted frequently, even in subjects with asthma whose disease was suboptimally controlled. In repeated measures analyses of people with asthma not taking an ICS, 22% of subjects had sputum eosinophilia on every occasion (persistent eosinophilia); 31% had eosinophilia on at least one occasion (intermittent eosinophilia); and 47% had no eosinophilia on every occasion (persistently noneosinophilic). Two weeks of combined antiinflammatory therapy caused significant improvements in airflow obstruction in eosinophilic asthma, but not in persistently noneosinophilic asthma. In contrast, bronchodilator responses to albuterol were similar in eosinophilic and noneosinophilic asthma. Conclusions: Approximately half of patients with mild-to-moderate asthma have persistently noneosinophilic disease, a disease phenotype that responds poorly to currently available antiinflammatory therapy.